2010
DOI: 10.1111/j.1468-2494.2010.00549_4.x
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosinase inhibitors isolated from the roots of Paeonia suffruticosa

Abstract: subsequent coloring due to its ability to take part in metal-induced radical chemistry (4). It is important to know where in the fibers these metals are located in order to either effectively remove these metals or control their chemistry. Nanoscale secondary ion mass spectrometry (NanoSIMS) has been used to locate the calcium and copper within hair that has been treated with a colorant and washed multiple times in tap water containing these ions. Untreated hair is used as a baseline standard material. Images … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…In a previous study, a gallic acid methyl derivative was shown to be a poorer inhibitor of the diphenolase activity of mushroom tyrosinase than gallic acid or kojic acid (Nithitanakool et al 2009 ). Meanwhile, the glycosylated forms of gallic acid (pentagalloyl glucopyranose) isolated from the seed kernels of Mangifera indica (Nithitanakool et al 2009 ) and the roots of Paeonia suffruticosa (Ding et al 2009 ) have been reported to be 16 times stronger than gallic acid for the inhibition of mushroom tyrosinase in a non-competitive inhibition manner. The previous studies correlated well with this finding that glycosylated gallic acid (1.23 mM) showed a slightly stronger whitening effect with a lower Ki value than gallic acid itself (1.98 mM) by mixed noncompetitive inhibition, instead of competitive-type inhibition (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, a gallic acid methyl derivative was shown to be a poorer inhibitor of the diphenolase activity of mushroom tyrosinase than gallic acid or kojic acid (Nithitanakool et al 2009 ). Meanwhile, the glycosylated forms of gallic acid (pentagalloyl glucopyranose) isolated from the seed kernels of Mangifera indica (Nithitanakool et al 2009 ) and the roots of Paeonia suffruticosa (Ding et al 2009 ) have been reported to be 16 times stronger than gallic acid for the inhibition of mushroom tyrosinase in a non-competitive inhibition manner. The previous studies correlated well with this finding that glycosylated gallic acid (1.23 mM) showed a slightly stronger whitening effect with a lower Ki value than gallic acid itself (1.98 mM) by mixed noncompetitive inhibition, instead of competitive-type inhibition (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Although melanin mainly plays a photoprotective role, the accumulation of abnormal amounts of melanin in different parts of the skin, results in pigmented patches on skin, poses as an esthetic problem. Therefore, several studies have been carried out to identify methods of inhibition of tyrosinase activity and the prevention of abnormal pigmentation (Ding et al, 2009;Chang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Because tyrosinase is a rate-limiting enzyme related to the first two steps of melanogenesis, agents possessing tyrosinase inhibitory activity can be regarded as potential candidates for a depigmentation strategy [ 39 ]. Therefore, tyrosinase activity was analyzed for evaluation of the involved mechanisms of VARM and its solvent fractions-induced antimelanogenesis in B16F10 cells.…”
Section: Discussionmentioning
confidence: 99%